Fe(III) reduction during pyruvate fermentation by Desulfotomaculum reducens strain MI‐1. Issue 1 (27th November 2013) - Dalla Vecchia, E.; Suvorova, E. I.; Maillard, J.; Bernier‐Latmani, R.
Abstract Desulfotomaculum reducens MI‐1 is a Gram‐positive, sulfate‐reducing bacterium also capable of reducing several metals, among which is Fe(III). Very limited knowledge is available on the potential mechanism(s) of metal reduction among Gram‐positive bacteria, despite their preponderance in the microbial communities that inhabit some inhospitable environments (e.g., thermal or hyperthermal ecosystems, extreme pH or salinity environments, heavy metal or radionuclide contaminated sediments). Here, we show that in the presence of pyruvate, this micro‐organism is capable of reducing both soluble Fe(III)‐citrate and solid‐phase hydrous ferric oxide, although growth is sustained by pyruvate fermentation rather than Fe(III) respiration. Despite the fact that Fe(III) reduction does not support direct energy conservation, D. reducens uses it as a complementary means of discarding excess reducing equivalent after H2 accumulation in the culture headspace renders proton reduction unfavorable. Thus, Fe(III) reduction permits the oxidation of greater amounts of pyruvate than fermentation alone. Fe(III) reduction by D. reducens is mediated by a soluble electron carrier, most likely riboflavin. Additionally, an intracellular electron storage molecule acts as a capacitor and accumulates electrons during pyruvate oxidation for slow release to Fe(III). The reductase responsible for the transfer of electrons from the capacitor to the soluble carrier has not been identified, but data presented here argue against the involvement of c‐type cytochromes.